Sebaceous adenitis in Swedish dogs, a retrospective study of 104 cases - Egenvall Agneta; Bergvall Kerstin; Hernblad Tevell Elisabeth (Acta Veterinaria Scandinavica, 2008)
Abstract Background Sebaceous adenitis (SA) is an uncommon, immune mediated skin disease in dogs. The aim was to retrospectively investigate SA in dogs in Sweden with respect to breed, sex and age distribution. A second aim was to retrospectively compare clinical signs in dogs with generalized SA and to estimate the survival after diagnosis in the English springer spaniel, standard poodle and the akita. Methods In total 34 Swedish veterinarians contributed with 104 clinically and histologically verified SA cases. Breed, gender and age at diagnosis were registered for each case. The degree of clinical signs at time for diagnosis and at follow-up and information about treatments, concurrent diseases and euthanasia were recorded for the springer spaniels, standard poodles and akitas using a standardized questionnaire. Results A total of 104 cases of SA were included; most cases were recorded for the springer spaniel (n = 25), standard poodle (n = 21) and the akita (n = 10). These three breeds, together with the lhasa apso and the chow-chow, were the most common when national registry data from the Swedish Board of Agriculture and Swedish Kennel Club were considered. The mean age at diagnosis was 4.8 years. The proportion of males was 61%. When the springer spaniels, standard poodles and the akitas with generalized signs were compared (n = 51), the spaniels showed significantly more severe clinical signs than the poodles at diagnosis regarding alopecia, seborrhoea, pyoderma and the overall severity of clinical signs. At follow-up, the degree of clinical signs for otitis externa and pyoderma differed significantly between the breeds. The estimated median survival time was 42 months. In dogs where data regarding survival was available at the end of the study (n = 44), SA was reported to be the reason for euthanasia in 14 dogs, whereof 7 within 24 months after diagnosis. Conclusion The result of this study implicates that the English springer spaniel is a breed predisposed to SA and that it has more severe clinical signs than the standard poodle. A large proportion of the dogs (spaniel, poodle and akita) investigated regarding survival were reported to have been euthanized to great extent due to the disease.